Hydrologic alterations impact plant litter decay rate and ecosystem resilience in Mojave wetlands. Issue 5 (20th May 2019) - Castle, Stephanie; Rejmánková, Eliška; Foley, Janet; Parmenter, Steve
Abstract : Understanding ecosystem processes is vital for effective restoration of degraded ecosystems, especially wetlands. Restoration has become a necessity for management and conservation of the federally endangered Amargosa vole ( Microtus californicus scirpensis ) endemic to small, bulrush ( Schoenoplectus americanus ) dominated wetlands in the Mojave Desert. Recent data indicate catastrophic decrease of the vole population and its habitat from local alterations to hydrology, combined with diminished decomposition rates of bulrush, persistence of plant litter, and minimal plant growth except along narrow margins along stream edges. We conducted a series of three field and one greenhouse experiment(s) testing the effect of (1) moisture level on plant decay rate, (2) litter removal on plant regeneration, (3) the interactive effect of litter removal and moisture level increase on plant regeneration, and (4) potential germination rate of bulrush seeds under multiple hydrologic regimes to understand how hydrologic alteration and litter decay ultimately influences marsh regeneration. Results revealed decrease in water level caused a 20‐fold reduction in decomposition rates of a degraded marsh. Litter removal alone and in combination with water table restoration significantly and positively affected bulrush resprouting ( p < 0.0001 for both). Seed bank experiments showed high rates of germination in saturated and flooded soil conditions, emphasizing the potential role of seedlings in ecosystem recovery. This study shows how the interaction of hydrologic change and decreased decomposition can shift an ecosystem toward limits of resilience. These results inform restoration strategies in arid‐region wetlands dominated by plants with slow litter decay where strategic litter removal may beneficially increase plant growth.